2011
DOI: 10.1371/journal.pone.0028755
|View full text |Cite
|
Sign up to set email alerts
|

A Picture on the Wall: Innovative Mapping Reveals Cold-Water Coral Refuge in Submarine Canyon

Abstract: Cold-water corals are azooxanthellate species found throughout the ocean at water depths down to 5000 m. They occur in patches, reefs or large mound structures up to 380 m high, and as ecosystem engineers create important habitats for a diverse fauna. However, the majority of these habitats are now within reach of deep-sea bottom trawling. Many have been severely damaged or are under threat, despite recent protection initiatives. Here we present a cold-water coral habitat type that so far has been overlooked –… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
144
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 158 publications
(154 citation statements)
references
References 36 publications
9
144
0
1
Order By: Relevance
“…Although particulate organic carbon (POC) is directly related to surface production, the preliminary results from the SAPs demonstrate that some areas within the canyon are subject to higher organic input than others. When the POC composition was analysed it was found that the eastern and western branch had different molecular signatures (Huvenne et al, 2011). Changes in the composition of POC input may influence the community structure of the Whittard Canyon, as seen, for instance, on the adjacent abyssal plain (Billett et al, 2001(Billett et al, , 2010.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although particulate organic carbon (POC) is directly related to surface production, the preliminary results from the SAPs demonstrate that some areas within the canyon are subject to higher organic input than others. When the POC composition was analysed it was found that the eastern and western branch had different molecular signatures (Huvenne et al, 2011). Changes in the composition of POC input may influence the community structure of the Whittard Canyon, as seen, for instance, on the adjacent abyssal plain (Billett et al, 2001(Billett et al, , 2010.…”
Section: Discussionmentioning
confidence: 99%
“…The amalgamation of these factors means canyons are often thought of as areas of enhanced biodiversity Vetter et al, 2010). However, very little work has occurred on the biological assemblages and their community structure within canyons, especially cold-water coral assemblages (Huvenne et al, 2011). The present study seeks to increase knowledge on the distribution of deep-sea corals within submarine canyons, focussing on the Whittard Canyon system on the continental margin in the NE Atlantic.…”
Section: Introductionmentioning
confidence: 99%
“…Submarine canyons are widespread complex features along continental margins and are pathways for sediment transport to the deep basins (Piper and Savoye, 1993;Wynn et al, 2007;Palanques et al, 2012), They play a key role in hydrography, biogeochemistry and carbon cycle dynamics (Epping et al, 2002;Canals et al, 2006;Huvenne et al, 2011). Despite their importance, the processes of start-up, evolution and maintenance of submarine canyons remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…The other habitats not discussed in this paper are the deep coldwater coral colonies in canyons Huvenne et al, 2011Huvenne et al, , 2012. Perched under overhanging cliffs or high on rocky spurs in highly stressed environments, they form significant refuges, but again they are in general not in a position to develop to the giant build-ups further considered here.…”
Section: Cold-water Coral Reefs In Canyons and On Glacial Marginsmentioning
confidence: 96%